ESTABILIZAÇÃO DE SOLO DE BAIXA CONSISTÊNCIA COM RESÍDUO PROVENIENTE DE PLANTA DE DESSULFURAÇÃO DOS GASES DE COMBUSTÃO - Marin, Alana Costa (2022)
Based on the need to improve very soft soils, research have been trying to enable the sustainable application of alternative stabilizers to Portland cement in soil chemical stabilization processes. There is a wide range of materials that can be studied for stabilization by providing an increase in strength or just maintaining it while directly reducing the amounts of cement and indirectly in the emissions of Carbon Dioxide (CO2). One of these materials is the residue from flue-gas desulfurization (FGD) plants in industries that use coal in energy production, such as steel industry. This research aimed to evaluate the FGD residue in the stabilization of a very soft clay through the incorporation of 15% of stabilizers in dry soil mass, individually or combined with Portland cement or ground blast furnace slag. For the incorporation of the residue to be evaluated, physical parameters such as moisture content, apparent density, liquid and plastic limit, mechanical parameters such as unconfined and undrained compressive strength and microstructural parameters were determined through X-ray diffraction (XRD) analyzes at different curing period. The results showed that the incorporation of FGD residue tended to decrease the soil moisture content, increase the apparent density and increase the resistance to unconfined compressive strength, up to 3550 times, when compared to soil without additives. The liquid and plastic limits tests indicated changes in the pure soil from the insertion of the stabilizing agents and the XRD analyses indicated the formation of hydrated and carbonated products responsible for the increase of mechanical resistance.